Interfaith Tolerance and Its Relevance to the Indonesian Diversity: A Study on Ibn ʿĀshūr’s al-Taḥrīr wa al-Tanwīr - Moh. Abdul Kholiq Hasan (Universitas Islam Negeri Mataram, 2018)
Indonesia is a biggest Muslim, and yet multi-cultural, country. Religious tolerance is a key issue for harmony, and correct understanding of this principle is highly important. Maqāṣid approach serves one of the alternatives for such understanding. This study aims to elucidate the concept of interfaith tolerance from the perspective of the maqāṣid offered by Ibn ʿĀshūr‘s interpretation and analyze its relevance to the context of Indonesian diversity. This study is based on his work al-Taḥrīr wa al-Tanwīr and finds several important principles of interreligious tolerance from the perspective of the Qur’an. As a Muslim reformer, Ibn ʿĀshūr sees that tolerance is one crucial issue that religious followers are now facing. Grounded on the maqāṣid approach, he finds several principles of interreligious relation from the Quranic verses. These principles fit to the highest objective of Islamic law (maqāṣid al-sharīʿa). These include drawing the common good and leaving away the damage, egalitarian, justice, conscience and freedom. These principles in the context of Indonesia are important and necessary in order to maintain harmony among religious people and the unity of the Republic of Indonesia.